Luminescent Thin Films Enabled by CsPbX3 (X=Cl, Br, I) Precursor Solution. Issue 25 (28th March 2022) - Liu, Yue; Wang, Yuxiang; Cheng, Haoran; Ma, Zheng; Li, Qian; Wang, Gang; Pan, Daocheng; Wang, Limin; Ming, Jun
Abstract: Inorganic cesium lead halide perovskite nanocrystals are candidates for lighting and display materials due to their outstanding optoelectronic properties. However, the dissolution issue of perovskite nanocrystals in polar solvents remains a challenge for practical applications. Herein, we present a newly designed one‐step spin‐coating strategy to prepare a novel multicolor‐tunable CsPbX3 (X=Cl, Br, I) nanocrystal film, where the CsPbX3 precursor solution was formed by dissolving PbO, Cs2 CO3, and CH3 NH3 X into the ionic liquid n‐butylammonium butyrate. The as‐designed CsPbX3 nanocrystal films show high color purity with a narrow emission width. Also, the blue CsPb(Cl/Br)3 film demonstrates an absolute photoluminescence quantum yields (PLQY) of 15.6 %, which is higher than 11.7 % of green CsPbBr3 and 8.3 % of red CsPb(Br/I)3 film. This study develops an effective approach to preparing CsPbX3 nanocrystal thin films, opening a new avenue to design perovskite nanocrystals‐based devices for lighting and display applications. Abstract : A new soluble CsPbX3 precursor to in‐situ prepare luminescent CsPbX3 nanocrystal film in the air readily was designed. The composition of the CsPbX3 NCs films can be tuned by changing the solution precursors, allowing obtaining a high color purity and a narrow emission width.